2015
DOI: 10.1007/s00239-015-9690-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Eukaryotic DNA Polymerases via Interaction Between Cells and Large DNA Viruses

Abstract: B-family DNA-directed DNA polymerases are DNA replication enzymes found in Eukaryota, Archaea, large DNA viruses, and in some, but not all, bacteria. Several polymerase domains are conserved among the B-family DNA polymerases from these organisms, suggesting that the B-family DNA polymerases evolved from a common ancestor. Eukaryotes retain at least three replicative B-family DNA polymerases, DNA polymerase α, δ, and ε, and one translesion B-family DNA polymerase, DNA polymerase ζ. Here, we present molecular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…Interestingly, Cafeteria roenbergensis virus, like many mimiviruses, contains a unique star-like structure at one end of the virion ( Colson et al, 2011 ), whereas Pyramimonas orientalis virus does not ( Sandaa et al, 2001 ). As mentioned above, after re-analysis of viral mRNA sequences from our previous work on NCLDVs in corals and Symbiodinium , we found that another diagnostic gene for this candidate Family ( Takemura et al, 2015 ), DNA polymerase B, also annotates to Pyramimonas orientalis virus. Therefore, given that: (1) our NCLDV lacks a star-shaped structure and is genetically similar to the Pyramimonas orientalis clade of megaviruses based on phylogenetic reconstruction of a diagnostic gene (MutS), and (2) similarities to this viral clade have previously been recovered from both corals and Symbiodinium cultures ( Correa et al, 2013 ), the most parsimonious interpretation of these physical and genetic data is that the Symbiodinium -associated megavirus in this study is a cosmopolitan relative of the Pyramimonas orientalis megaviruses.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, Cafeteria roenbergensis virus, like many mimiviruses, contains a unique star-like structure at one end of the virion ( Colson et al, 2011 ), whereas Pyramimonas orientalis virus does not ( Sandaa et al, 2001 ). As mentioned above, after re-analysis of viral mRNA sequences from our previous work on NCLDVs in corals and Symbiodinium , we found that another diagnostic gene for this candidate Family ( Takemura et al, 2015 ), DNA polymerase B, also annotates to Pyramimonas orientalis virus. Therefore, given that: (1) our NCLDV lacks a star-shaped structure and is genetically similar to the Pyramimonas orientalis clade of megaviruses based on phylogenetic reconstruction of a diagnostic gene (MutS), and (2) similarities to this viral clade have previously been recovered from both corals and Symbiodinium cultures ( Correa et al, 2013 ), the most parsimonious interpretation of these physical and genetic data is that the Symbiodinium -associated megavirus in this study is a cosmopolitan relative of the Pyramimonas orientalis megaviruses.…”
Section: Discussionsupporting
confidence: 54%
“…In the phylogenetic tree of DNAPs, the magrovirus polymerases cluster with the halovirus DNAPs [17, 26], and, together, these viral polymerases are related to archaeal DNApolB III that is involved in lagging strand replication (Figure 1B). This gene is apparently subject to frequent horizontal transfer among archaea that is likely to be at least partially mediated by viruses [27, 28], so that the DNApolB III phylogeny does not follow the archaeal evolutionary tree. Groups A and C that were delineated by analysis of morphogenetic genes retain monophyly in the DNAP tree (Figure 1B), whereas group B splits between two branches, one of which is affiliated with group A (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…7.0.14) (26) with default parameters. A maximum-likelihood inference program and the LG model was used as a substitution model with discrete gamma-distributed rate variations and a proportion of sites being invariant (24) to construct the phylogenetic tree. In order to estimate branch support, 100 bootstrap replications were performed.…”
Section: Methodsmentioning
confidence: 99%